LEDGF(1-326) decreases P23H and wild type rhodopsin aggregates and P23H rhodopsin mediated cell damage in human retinal pigment epithelial cells. - Rinku Baid; Robert I Scheinman; Toshimichi Shinohara; Dhirendra P Singh; Uday B Kompella (PLoS ONE)
Background P23H rhodopsin, a mutant rhodopsin, is known to aggregate and cause retinal degeneration. However, its effects on retinal pigment epithelial (RPE) cells are unknown. The purpose of this study was to determine the effect of P23H rhodopsin in RPE cells and further assess whether LEDGF(1-326), a protein devoid of heat shock elements of LEDGF, a cell survival factor, reduces P23H rhodopsin aggregates and any associated cellular damage. Methods ARPE-19 cells were transiently transfected/cotransfected with pLEDGF(1-326) and/or pWT-Rho (wild type)/pP23H-Rho. Rhodopsin mediated cellular damage and rescue by LEDGF(1-326) was assessed using cell viability, cell proliferation, and confocal microscopy assays. Rhodopsin monomers, oligomers, and their reduction in the presence of LEDGF(1-326) were quantified by western blot analysis. P23H rhodopsin mRNA levels in the presence and absence of LEDGF(1-326) was determined by real time quantitative PCR. Principal findings P23H rhodopsin reduced RPE cell viability and cell proliferation in a dose dependent manner, and disrupted the nuclear material. LEDGF(1-326) did not alter P23H rhodopsin mRNA levels, reduced its oligomers, and significantly increased RPE cell viability as well as proliferation, while reducing nuclear damage. WT rhodopsin formed oligomers, although to a smaller extent than P23H rhodopsin. Further, LEDGF(1-326) decreased WT rhodopsin aggregates. Conclusions P23H rhodopsin as well as WT rhodopsin form aggregates in RPE cells and LEDGF(1-326) decreases these aggregates. Further, LEDGF(1-326) reduces the RPE cell damage caused by P23H rhodopsin. LEDGF(1-326) might be useful in treating cellular damage associated with protein aggregation diseases such as retinitis pigmentosa.